2021
DOI: 10.1177/0967391121998490
|View full text |Cite
|
Sign up to set email alerts
|

Optimal radiation shielding capacity and thermal properties of poly(methyl methacrylate) films enhanced with different metal complexes

Abstract: Samples of pure poly(methyl methacrylate) (PMMA) and PMMA enhanced with metal complexes of Zn, Cd, and Hg were synthesized via catalytic chain transfer polymerization. Structural analysis, by means of XRD, showed the amorphous nature of the studied samples which meant high homogenous dissolution of the metals (Zn, Cd and Hg) into the polymer matrix. Density values increased linearly with respect to atomic radius of the incorporated metals. Addition of such elements causes an increase in mass attenuation coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Bardak et al reported that PVAc is only partly crystalline, where two crystalline peaks at 12.5° and ~ 21° were found in its XRD pattern 13 . In addition, Saudi et al 10 also found two peaks at ~ 26 and 48 in the XRD pattern of PMMA. When more LaFeO 3 (0.5–10 wt%) was loaded, the intensity of these peaks went down without moving their centers, which shows that the matrix became more disorganized.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Bardak et al reported that PVAc is only partly crystalline, where two crystalline peaks at 12.5° and ~ 21° were found in its XRD pattern 13 . In addition, Saudi et al 10 also found two peaks at ~ 26 and 48 in the XRD pattern of PMMA. When more LaFeO 3 (0.5–10 wt%) was loaded, the intensity of these peaks went down without moving their centers, which shows that the matrix became more disorganized.…”
Section: Resultsmentioning
confidence: 92%
“…Polymer nanocomposites are multifunctional materials that can be applied for catalytic reduction of pollutants, environmental applications, food backing, and various medical and pharmaceutical purposes 4 6 . Moreover, when compared to some alloys and bioglasses used in space applications 7 10 , these polymer nanocomposite materials can shield radiation well while having lower mass and density, being easy to handle, being flexible, and producing less secondary radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation